Tinjauan Nilai Ekologi Profetik dalam Tunjuk Ajar Melayu Karya Tenas Effendy - Firman Firman; Doni Saputra; Annisa Fitri Azzahra (STAIN Sultan Abdurrahman Kepulauan Riau, 2025)
The global environmental crisis demands an ecological ethics framework that is not merely rational and technical, but also deeply rooted in cultural and spiritual values. This study aims to explore and analyze ecological values found in Tunjuk Ajar Melayu by Tenas Effendy as a foundation for environmental ethics grounded in local wisdom and aligned with Islamic teachings, particularly the hadiths of the Prophet Muhammad (peace be upon him). This research employs a qualitative approach using content analysis and intertextual analysis of Tunjuk Ajar Melayu, identifying ecologically themed verses and comparing them with hadiths that convey parallel meanings. This approach is intended to reveal the interconnection between customary traditions (adat) and Islamic law (shar?‘ah) as a basis for environmental ethics. The findings indicate that the ecological values in Tunjuk Ajar Melayu are structured around three main pillars: humans as stewards (khal?fah) responsible for nature, humans as preservers and balancers of the environment, and awareness of the destructive consequences of environmental degradation. These pillars function not only as customary ethical norms but also embody a spiritual dimension that frames environmental preservation as an act of worship and moral responsibility within an Islamic perspective.